THURLER, Ana Liési. Em nome da mãe: o não reconhecimento paterno no Brasil. - Bensusan, Hilan (Revista Estudos Feministas, 2012)
THURLER, Ana Liési. Em nome da mãe: o não reconhecimento paterno no Brasil.